IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY PT PERTAMINA DALAM MENDUKUNG KONSERVASI SUMBER DAYA ALAM DI MINANGKABAU - Mayasari, Silvina (Universitas Islam Syekh Yusuf, 2023)
This study aims to see how the Implementation of PT Pertamina's Corporate Social Responsibility in Supporting the Conservation of Natural Resources in Minangkabau. Corporate Social Responsibility is defined as the company's responsibility to stakeholders to act ethically, minimize negative impacts and maximize positive impacts which include economic, social and environmental aspects (triple bottom line) in order to achieve sustainable development goals. The research method in this study is a descriptive qualitative method that focuses on the Implementation of PT Pertamina's Corporate Social Responsibility in Supporting the Conservation of Natural Resources in Minangkabau. Data Collection Techniques Data collection techniques in qualitative research are observation, literature, interviews and documentation studies. In this CSR program partnering with the West Sumatra Natural Resources Conservation Center (BKSDA). This activity focuses on handling conflicts that occur between people and wild animals. From the implementation of this CSR activity PT Pertamina is implemented in the form of Community Assistance, providing assistance by considering the needs that are really needed by the community. In practice, this wildlife conservation program is carried out by PT Pertamina in collaboration with the West Sumatra Natural Resources Conservation Agency (BKSDA). While the level of CSR carried out in wildlife conservation is Philanthropy, CSR program activities that help solve problems partially. Keywords: Implementation, Corporate Social Responsibility, community assistance, Philanthropy